MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA MELALUI PEMBELAJARAN DENGAN GOOGLE MEET - Nur Latifah; Andhika Ayu Wulandari; Suratno Suratno (Absis: Mathematics Education Journal, 2020)
This objective of this study is to improve student learning outcome on mathematics using the Google Meet Application in class X MIPA 3 SMA 1 Tawangsari, with 36 students which consist of 8 male and 28 female students. The technique of collecting data uses tests. Data analysis techniques are data reduction, presentation, and conclusion drawing. From the analizes, it can be seen from the increase in student learning outcomes from the pra siklus, siklus I to siklus II. This can be concluded that the use of the Google Meet application can improve student learning outcomes in mathematics in class X MIPA 3 SMA 1 Tawangsari.